Analysis of cellular responses to native and recombinant proteins of Cowdria ruminantium - Totte, P.; McKeever, Declan J.; Jongejan, F.; Barbet, A.; Mahan, S.M.; Mwangi, D.; Bensaid, A. (Wiley, 1998)
The response of peripheral blood mononuclear cells (PBMC) collected from cattle immunized with killed C. ruminantium to MAP1, MAP1-B, MAP2 and to a lysate of Cowdria was characterized in vitro. CD4+ T lymphocytes responded strongly to Cowdria lysates while B cells and gamma delta T cells proliferated in response to recombinant proteins. Short-term cell lines derived from PBMC using Cowdria lysates were >90% CD4+ and did not respond to any of the recombinant proteins. Restimulation of PBMC with MAP1, MAP1-B, and MAP2 proved difficult, and cultures usually stopped proliferating after 2 to 3 weeks. Only 1 cell line could be generated using MAP1 and it was composed of 85% gamma delta T cells. This study indicates that in animals immunized with killed Cowdria, proteins other than the serologically immunodominant MAP1 and MAP2 are strongly immunogenic for T lymphocytes.